Brazilian women in the sports press: a case study - Knijnik, J. D.; Sturmer Soares de Souza, J. (Journal of Human Sport & Exercise, 2011)
The media is a powerful tool in creating sports legends. However, international studies have proved that the media tends to favor male athletes and their feats and neglects female sports players. The main purpose of this paper is to determine how many articles one of the most important daily newspapers in Brazil published about male and female athletes. The data was gathered over a number of months at the beginning of this decade. The analysis demonstrated that men usually are mentioned much more frequently than women, that journalists tend to write more about the appearance of female athletes than about their real talents for sport. The findings lead to the conclusion that gender inequality in sport in Brazil is common and that the media, instead of contributing to the decrease in levels of gender inequality, is contributing to this inequality in wider society.